Prevalence Of Flat Foot In Dominant Lower Limb Among Professional Kathak Dancers - Shukla, Chaitrali Omkar; Bhat, Aakanksha (Journal of Neonatal Surgery, 2025)
Background: Kathak, a classical Indian dance form which includes repeatedly rhythmical footwork spinning movements often perform barefoot on hard surface. Prolonged and intense training may lead to biomechanical changes in the foot, including flat foot. Not only kathak but the all classical dance forms have their own character of presentation which may lead to the postural changes. Methods: A cross-sectional study was conducted among professional Kathak dancers in Sangli, Miraj and Kolhapur city. Total 107 samples are included according to inclusion criteria which consist of age between 16-42 years, female gender and has experience of more than 5 years; and individual who had previous surgery of foot, recent trauma to foot/ankle and congenital flatfoot are excluded . The study focuses on dominant lower limb, so to find dominant lower limb kick test is used. The deviation foot is determined by Foot Posture Index (FPI) and Clark’s angle. Results: Result shows 84 positive and negative 23 in individuals out of 107 individuals which results in significant prevalence of flat foot in dominant lower limb among Kathak dancers. Percentage of positive and negative results are 78.50% and 21.50% respectively so, the prevalence of the study is 78.50%. mean values of age, year of experience, practicing hours per day FPT and Clark’s angle was calculated and noted in tables. Conclusion: The study concludes that high frequency Kathak practice may contribute in postural deviation and development of flatfoot. Preventive strategies such as foot strengthening exercises, Modified training surfaces, and orthotic support may help reduce the risk. Further research is needed to explore long term biomechanical impacts and gender specific differences.